Zeitschrift für Naturforschung C : A Journal of Biosciences (De Gruyter, 1973)
A Journal of Biosciences: Zeitschrift für Naturforschung C (ZNC) is an international scientific journal for the emerging field of natural and natural-like products. ZNC publishes original research on the isolation, bio-chemical synthesis and bioactivities of natural products, their biochemistry, pharmacology, biotechnology, and biological activity and innovative developed computational methods for predicting their structure and/or function.